2022
DOI: 10.1088/2516-1075/ac49f5
|View full text |Cite
|
Sign up to set email alerts
|

Moiré engineering of spin–orbit coupling in twisted platinum diselenide

Abstract: We study the electronic structure and correlated phases of twisted bilayers of platinum diselenide using large-scale ab initio simulations combined with the functional renormalization group. PtSe2 is a group-X transition metal dichalcogenide, which hosts emergent flat bands at small twist angles in the twisted bilayer. Remarkably, we find that moiré engineering can be used to tune the strength of Rashba spin-orbit interactions, altering the electronic behavior in a novel manner. We reveal that an effective tri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 106 publications
0
9
0
Order By: Relevance
“…We note that alternative patching schemes with very high computational costs could potentially remedy quantitative discrepancies between N -patch and TUFRG, e.g., by employing a regular discretization of the full Brillouin zone, cf. [57].…”
Section: Discussionmentioning
confidence: 99%
“…We note that alternative patching schemes with very high computational costs could potentially remedy quantitative discrepancies between N -patch and TUFRG, e.g., by employing a regular discretization of the full Brillouin zone, cf. [57].…”
Section: Discussionmentioning
confidence: 99%
“…The ideas of "twistronics", where the control over electric phases is achieved by the relative rotation between 2D layers of van der Waals materials, [36][37][38][39][40][41][42][43] have recently motivated a related paradigm of twisted bilayer structures in magnetic systems. [44] While magneto chirality has typically been tailored at the intrinsic structural level by the proper selection of specific materials and composition, [19] recently, it has been shown that the relative twist of bilayers with antiferromagnetic and ferromagnetic spin couplings in magnetic insulators, can give rise to noncollinear magnetic textures for small twist angles.…”
Section: Introductionmentioning
confidence: 99%
“…The library is based on a general model interface (cf. Section 3), and three different computation backends: (i) grid-FRG [19,20], (ii) truncated unity FRG (TU 2 FRG) [21][22][23], and (iii) orbital space N -patch FRG [24][25][26]. Each performs different approximations of the central equations, resulting in different numerical complexity, as detailed in Appendix D. This paper is designed as a hands-on introduction to the usage of divERGe.…”
Section: Introductionmentioning
confidence: 99%